Sympathetic Nerve Function Status in Postmenopausal Women - Naher, Latifa Afrin Dill; Begum, Noorzahan; Ferdousi, Sultana; Begum, Shelina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2010)
Background: Postmenopausal women usually suffer from increased incidence of cardiovascular diseases than premenopausal women. Alterations in autonomic nerve functions often develop in this group of women that commonly affect cardiac vagal control and usually associated with sympathetic hyperactivity. Objectives: To observe the sympathetic nerve function status in postmenopausal women and their relationships with serum estrogen level. Methods: This cross sectional study was carried out in the Department of Physiology, BSMMU, Dhaka from 1st January to 31st December 2007. A total number of 60 apparently healthy subjects of whom 30 were postmenopausal women with age ranged from 45-60 years(group B) and 30 were premenopausal women with age ranged from 20-30 years (group A) were enrolled. Premenopausal women were studied during follicular phase of menstrual cycle. Two simple autonomic nerve function tests, rise of diastolic blood pressure (DBP) during hand grip and fall of systolic blood pressure (SBP) on standing were done to assess sympathetic activity and serum estrogen level was measured in both the groups. Data were analysed by unpaired t test and Pearson correlation coefficient test. Results: Mean resting SBP and DBP were significantly higher (p<0.001) in postmenopausal women than premenopausal women. The mean value of estrogen was significantly (p<0.001) lower in group B (postmenopause) than those in group A (premenopause). Fall in systolic blood pressure after standing was significantly (p<0.001) higher and rise in diastolic blood pressure after sustained handgrip was significantly (p<0.001) lower in postmenopausal women than those in premenopausal women during their follicular phase of menstrual cycle. Again, rise in diastolic blood pressure after sustained handgrip and fall in systolic blood pressure after standing showed (p>0.05) negative correlation with estrogen level in the postmenopausal women which was statistically not significant. In addition, regression analysis further revealed significant association of sympathetic activity with estrogen level and age in postmenopausal women. Conclusion: From this study it can be concluded that sympathetic activity is higher in postmenopausal women, which may be related to their low estrogen level and age as well. Key words: Postmenopause; sympathetic nerve functions; estrogen. DOI: 10.3329/jbsp.v5i1.5417 J Bangladesh Soc Physiol. 2010 June; 5(1): 40-45